Reactions of Epoxides with 3,3,4,4-Tetraethoxybut-1-yne Acetylide: Selective Formation of Propargylic and Homopropargylic Alcohols - Holmelid, Bjarte; Sydnes, Leiv K. (Synthesis, 2013)
3,3,4,4-Tetraethoxybut-1-yne acetylide (TEB–) reacted with several epoxides under a variety of conditions. When the acetylide counterion was lithium, nothing happened in the absence of ammonia and HMPA, but reaction of TEBLi with a mixture of oxirane and BF3 (oxirane/BF3 addition to the acetylide) followed by hydrolysis gave the expected homopropargylic alcohols in about 80% yield. When the counterion was MgBr+, oxirane-to-aldehyde rearrangement took place before the acetylide reacted and gave propargylic alcohols in good yields in all cases except one; the only exception was ethylene oxide, which gave the homopropargylic alcohol in 70% yield.
Keywords: epoxides; acetylides; counterions; oxirane rearrangement; homopropargylic alcohol; propargylic alcohols